An examination of behavioral treatment wording on acceptability and understanding. (1st March 2018) - Banks, Brea M.; Shriver, Mark D.; Chadwell, Mindy R.; Allen, Keith D.
Abstract : It has long been suggested that the words we use when describing treatments may affect treatment acceptability. However, previous research has focused largely on teachers or undergraduates, with mixed results. The purpose of this study was to evaluate how wording impacted the acceptability and understanding of a behavioral treatment described to parents of clinically referred children. Parents visiting an outpatient behavioral health clinic with their children were asked to watch a video description of a common behavioral intervention (time‐out) but were randomly assigned to one of three time‐out wording conditions: (a) technical terminology, (b) nontechnical terminology, or (c) popular terminology. Participants watched a video of a therapist describing time‐out and then completed a survey of treatment and therapist acceptability, as well as their comprehension of the procedure. Results indicate that the language used did not differentially affect parents' acceptability of the treatment or of the therapist. The language used did, however, affect parents' comprehension of the intervention. Results and implications are discussed.